Triangulation Method And Morphological Operations For Measurements Of Underwater Objects Using Stereo Vision - Rashid , Anith Nuraini Abd (2015)

(untitled)
This thesis improves the accuracy in detection and range estimation of any objects underwater by using stereo vision. Nowadays there are two major types of camera produced by the industry with the purposes of capturing underwater image or video. One is with built in waterproof camera while the other type of camera converted into waterproof camera with a waterproof housing. Therefore investigation is done on two scenario setups which built up to mimic these two camera condition. In the experiment, triangulation method is selected in order to evaluate the object distance of multiple locations. Image processing methods are used to measure size of the objects which are Sobel edge detector and morphological operations. From experimental results, it is observed that the average error of the triangulation methods and image processing improved with the correction made to the measurement results under the error of refraction. The most error improvement acquired is the first scenario which refracts from water into the air. Perimeter and area measurement accuracy influenced the most by the factor chose during edge detection where the pixel is sensitive in Sobel operator and morphological operations